Persepsi Ibu Menyusui terhadap Pemberian Asi Eksklusif di Wilayah Kerja Puskesmas Loa Duri - Putri Juliani; Joko Sapto Pramono; Andry Rachmadani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Exclusive breastfeeding is a proven strategy for reducing infant morbidity and preventing stunting, yet national and local coverage in Indonesia remains below the government target. In the working area of Puskesmas Loa Duri, Kutai Kartanegara, coverage declined sharply from 82% in 2022 to only 21% in 2024, despite the well-documented benefits of breast milk. This qualitative phenomenological study aimed to explore breastfeeding mothers' perceptions of exclusive breastfeeding using the Health Belief Model, focusing on perceived susceptibility and perceived severity. Data were collected through in-depth interviews, non-participatory observation, and documentation involving eight informants: one key informant (a paediatrician), six main informants (breastfeeding mothers), and one supporting informant (a family member), selected through purposive sampling. Data were analysed thematically until saturation was reached. The results showed that most mothers perceived infants who were not exclusively breastfed as more vulnerable to illness, particularly infections and digestive disorders, although awareness of long-term consequences such as stunting was still limited among several informants. Mothers generally held strong intentions to breastfeed exclusively, reinforced by support from husbands, family, and health workers, and most reported no significant barriers to sustaining exclusive breastfeeding. These findings indicate that perception, family support, and health-worker counselling are key determinants of exclusive breastfeeding practice, and highlight the need for continuous, community-based health promotion to improve coverage in the study area.